The conscientious worker: Changing management conceptions of the ideal worker in warehouse labour regimes - Tom Barnes (Work Organisation, Labour and Globalisation)
Employer discourse is an under-researched element of scholarship on labour regimes, which has tended to dismiss employer views as self-serving or duplicitous. In response, this article argues that employer discourse should be taken more seriously as a response to real-world transformations in markets, supply chains, technologies and labour markets. Evidence is drawn from Australia’s largest cities, where experimentation with automation has led to a combination of different labour processes alongside an emphasis on accuracy, as well as speed, in each. Drawing on interviews with managers, this article documents the emergence of a new image of the ideal worker as one who is more than simply flexible and agile, but also conscientious in observing the accuracy requirements of consumer fulfilment in contemporary warehousing.